Lactic Acid Bacteria Selection for Biopreservation as a Part of Hurdle Technology Approach Applied on Seafood - Wiernasz, Norman; Cornet, Josiane; Cardinal, Mireille; Pilet, Marie-France; Passerini, Delphine; Leroi, Françoise (Frontiers in Marine Science, 2017)
As fragile food commodities, microbial, and organoleptic qualities of fishery and seafood can quickly deteriorate. In this context, microbial quality and security improvement during the whole food processing chain (from catch to plate), using hurdle technology, a combination of mild preserving technologies such as biopreservation, modified atmosphere packaging, and superchilling, are of great interest. As natural flora and antimicrobial metabolites producers, lactic acid bacteria (LAB) are commonly studied for food biopreservation. Thirty-five LAB known to possess interesting antimicrobial activity were selected for their potential application as bioprotective agents as a part of hurdle technology applied to fishery products. The selection approach was based on seven criteria including antimicrobial activity, alteration potential, tolerance to chitosan coating, and superchilling process, cross inhibition, biogenic amines production (histamine, tyramine), and antibiotics resistance. Antimicrobial activity was assessed against six common spoiling bacteria in fishery products (Shewanella baltica, Photobacterium phosphoreum, Brochothrix thermosphacta, Lactobacillus sakei, Hafnia alvei, Serratia proteamaculans) and one pathogenic bacterium (Listeria monocytogenes) in co-culture inhibitory assays miniaturized in 96-well microtiter plates. Antimicrobial activity and spoilage evaluation, both performed in cod and salmon juice, highlighted the existence of sensory signatures and inhibition profiles, which seem to be species related. Finally, six LAB with no unusual antibiotics resistance profile nor histamine production ability were selected as bioprotective agents for further in situ inhibitory assays in cod and salmon based products, alone or in combination with other hurdles (chitosan, modified atmosphere packing, and superchilling).